2009
DOI: 10.5089/9781451873009.001
|View full text |Cite
|
Sign up to set email alerts
|

Do Workers' Remittances Promote Economic Growth?

Abstract: This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. Over the past decades, workers' remittances have grown to become one of the largest sources of financial flows to developing countries, often dwarfing other widely-studied sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(40 citation statements)
references
References 10 publications
1
37
1
1
Order By: Relevance
“…It can be shown that the impact of remittances on economic development was investigated in previous research using the category called "consumption". The direct and indirect effect of remittance on economic growth through consumption was argued by Barajas et al (2009), Giuliano and Ruiz-Arranz (2009), Ratha (2005), or Meyer and Shera (2017). For instance, Ratha (2005) points out the "consumption-smoothing" effect of remittance and considers them as a factor of sustainable economic growth.…”
Section: Empirical Model and Its Resultsmentioning
confidence: 99%
“…It can be shown that the impact of remittances on economic development was investigated in previous research using the category called "consumption". The direct and indirect effect of remittance on economic growth through consumption was argued by Barajas et al (2009), Giuliano and Ruiz-Arranz (2009), Ratha (2005), or Meyer and Shera (2017). For instance, Ratha (2005) points out the "consumption-smoothing" effect of remittance and considers them as a factor of sustainable economic growth.…”
Section: Empirical Model and Its Resultsmentioning
confidence: 99%
“…Rapoport (2002) stated that remittances are utilized as a source of finance for human and physical capital investment. Gapen et al, (2009) used ordinary least squares OLS and the fixed effect model; Catrinescu et al, (2008) used OLS; Cruz Zuniga (2011) used panel VAR; Ramirez (2013) applied FMOLS;and Hargreaves (1994) and Marwan et al, (2013) used the Johansen cointegration technique for checking the long-run effect of remittances on economic growth. One of the major problems with the Johansen cointegration technique is that it requires a large number of observations for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque el debate sobre el impacto de las remesas que una economía recibe a lo largo de un cierto periodo de tiempo, se ha centrado sobre si éstas pueden o no coadyuvar al crecimiento y desarrollo económico; bajo dicho contexto tanto Brown (2006) como Gapen, Barajas, Chami, Montiel, y Fullenkamp (2009), señalan que es indudable que las remesas constituyen un papel fundamental en los países en vías de desarrollo, puesto que una franja de su población percibe ingresos extraordinarios, los cuales pueden mejorar, aunque sea de forma marginal sus percepciones mensuales, que teóricamente significaría una mejora en la calidad de vida, sin embargo, dichos autores no comprueban empíricamente la relación del flujo de remesas con el crecimiento económico, por lo anterior, habrá que examinar el papel que juegan las remesas hacia el interior de la economía receptora, por ello es importante empezar con algunas definiciones de dichos ingresos.…”
Section: Introductionunclassified